An exploratory study on the emergency remote education experience of higher education students and teachers during the COVID‐19 pandemic. (18th May 2021) - Oliveira, Gabriella; Grenha Teixeira, Jorge; Torres, Ana; Morais, Carla
Abstract: The COVID‐19 pandemic situation has pushed many higher education institutions into a fast‐paced, and mostly unstructured, emergency remote education process. In such an unprecedented context, it is important to understand how technology is mediating the educational process and how teachers and students are experiencing the change brought by the pandemic. This research aims to understand how the learning was mediated by technology during the early stages of the pandemic and how students and teachers experienced this sudden change. Data were collected following a qualitative research design. Thirty in‐depth and semi‐structured interviews (20 students and 10 teachers) were obtained and analysed following a thematic analysis approach. Results provide evidence on the adoption of remote education technologies due to the pandemic with impacts on the education process, ICT platforms usage and personal adaptation. The emergency remote education context led to mixed outcomes regarding the education process. Simultaneously, ICT platforms usage was mostly a positive experience and personal adaptation was mostly a negative experience. These results bring new insights for higher education organizations on actions they could take, such as curating the learning experience with standard, institutional‐wide platforms, appropriate training for students and teachers, and suitable remote evaluation practices. Practitioner notes What is already known about this topic The COVID‐19 pandemic has pushed the world's education environment into an unstructured, emergency remote education process. There is a lack of understanding of how ICT tools mediated learning during pandemic's early stages and how actors experienced this sudden change. In technology‐mediated learning contexts, participant beliefs, knowledge, practices and the environment mutually influence one another and affect the lived experience. What this paper adds The paper identifies and characterizes the educational process, the technological tools used in this new educational setting and personal adaptation of higher education students and teachers during these unprecedented times. The results show the following: an increase in teacher–student interaction (outside classes), new opportunities and content development; difficulties in control evaluation fraud, constraints in attaining the desired learning outcomes and lack of training; resilience to adapt and adopt the new technologies, despite the negative personal experience lived in terms of productivity, motivation, workload and mental health. Implications for practice and/or policy The paper makes evidence‐based recommendations on how higher education institutions can leverage this experience to prepare for future disruptions and increase the use of ICT tools in their regular learning environment.